Transformation of Kapuas Riverside tourism village in Pontianak City: a study of TALC development and 6a tourism components of Kampung Caping - Muhammad Habibie; Lilis Listiyawati; Mochammad Musafa'ul Anam (Jurnal Pariwisata Pesona)
The growth of sustainable tourism requires a comprehensive understanding of destination development stages and the condition of its core components. This study aims to analyze the development stage of Kampung Caping based on the Tourism Area Life Cycle (TALC) model, evaluate the condition of the 6A tourism components, and formulate development strategies using the SOAR (Strengths, Opportunities, Aspirations, Results) framework. A qualitative descriptive approach was employed, with data collected through field observations, in-depth interviews, and documentation. The findings reveal that Kampung Caping is currently in the involvement stage of TALC, characterized by strong community engagement and the emergence of local institutional initiatives. The evaluation of the 6A components indicates strengths in cultural attractions, accessibility, and tourism activities, while limitations remain in terms of amenities and utilization of tour packages. Development strategies are focused on enhancing local assets, strengthening human resource capacity, fostering multi-sector collaboration, and organizing educational tourism events. This study contributes to the literature on community-based tourism development and offers an integrative analytical framework of TALC–6A–SOAR that can be replicated in similar destinations.